Analysis of A4gnt Knockout Mice Reveals an Essential Role for Gastric Sulfomucins in Preventing Gastritis Cystica Profunda. (October 2019) - Kawakubo, Masatomo; Komura, Hitomi; Goso, Yukinobu; Okumura, Motohiro; Sato, Yoshiko; Fujii, Chifumi; Miyashita, Masaki; Arisaka, Nobuhiko; Harumiya, Satoru; Yamanoi, Kazuhiro; Yamada, Shigenori; Kakuta, Shigeru; et al.
Gastric adenocarcinoma cells secrete sulfomucins, but their role in gastric tumorigenesis remains unclear. To address that question, we generated A4gnt / Chst4 double-knockout (DKO) mice by crossing A4gnt knockout (KO) mice, which spontaneously develop gastric adenocarcinoma, with Chst4 KO mice, which are deficient in the sulfotransferase GlcNAc6ST-2. A4gnt / Chst4 DKO mice lack gastric sulfomucins but developed gastric adenocarcinoma. Unexpectedly, severe gastric erosion occurred in A4gnt / Chst4 DKO mice at as early as 3 weeks of age, and with aging these lesions were accompanied by gastritis cystica profunda (GCP). Cxcl1, Cxcl5, Ccl2, and Cxcr2 transcripts in gastric mucosa of 5-week-old A4gnt / Chst4 DKO mice exhibiting both hyperplasia and severe erosion were significantly upregulated relative to age-matched A4gnt KO mice, which showed hyperplasia alone. However, upregulation of these genes disappeared in 50-week-old A4gnt / Chst4 DKO mice exhibiting high-grade dysplasia/adenocarcinoma and GCP. Moreover, Cxcl1 and Cxcr2 were downregulated in A4gnt / Chst4 DKO mice relative to age-matched A4gnt KO mice exhibiting adenocarcinoma alone. These combined results indicate that the presence of sulfomucins prevents severe gastric erosion followed by GCP in A4gnt KO mice by transiently regulating a set of inflammation-related genes, Cxcl1, Cxcl5, Ccl2, and Cxcr2 at 5 weeks of age, although sulfomucins were not directly associated with gastric cancer development: